PENINGKATAN KEAKTIFAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SKI MELALUI MODEL PEMBELAJARAN CTL (Penelitian di MTs. Kafa El-Madani Kabupaten Majalengka) - Andri Marta Sudirja; Hasan Basri (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2020)
The purpose of this research is to identify of the activiness of students in taking lessons in the history of islamic culture. The applicationof CTL models to increase the learning activiness of students and helf them to associate the material have been taught with their real world situation. To identify the factors that influence the students learning activiness. To know the results of applying the CTL model in the history of isamic culture. The research uses a qualitative approuch to assess the sources of data obtain in this research is information from the principal, the history of islamic culture teacher, students and researchers’ notes through observations in the field. The data collection techniques are carried out by interviews, observation and study of documentation of data sources at the research site. The data that has been obtained and analyzed and then to be concluded with a clear description. The result of this research indicates that : 1)the increasing student activity start from giving motivation by educator. 2)The effectiveness and the efficient learning through contextual teaching and learning (CTL) is important to be implemented so that studenats are more independent and responsible in the learning proccess. 3)Supporting factors in learning must be well prepared prepared and inhibiting factors must be evaluated carefully. 4)The result of the applicationof a positive indicated contextual learning model to increase the activiness and learning achievement of students.